Implementasi Kebijakan Pelayanan Online Administrasi Kependudukan Pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Sukabumi - Arsyad, Eriek Gunawan; Rachmawati, Ike (JPM MOCCI : Jurnal Pengabdian Masyarakat Ekonomi, Sosial Sains dan Sosial Humaniora, Koperasi, dan Kewirausahaan, 2024)
The purpose of this study is to evaluate how the Online Service policy is implemented in population administration services in Disdukcapil Sukabumi Regency and identify factors that encourage and hinder its implementation. The research method used is a qualitative approach with data collection through interviews, observation, and documentation. Research informants consisted of the Head of Population Administration, service counter officers, and applicants for population administration services in Disdukcapil Sukabumi Regency. Data analysis is carried out in a qualitative descriptive manner through data reduction, data presentation, and verification. The results showed that the implementation of Online Service policies is supported by effective communication, adequate resources, and a well-structured bureaucratic structure. Driving factors include authority in carrying out population administration services, planning programs, and supporting activities, as well as good coordination with regional apparatus organizations through Cooperation Agreements. However, there are obstacles such as the lack of optimal information technology-based public services, lack of integration and synchronization of population data between agencies, and the absence of technical guidelines from the Mayor Regulation in the implementation of Online Service policies. Other obstacles come from the community, such as lack of knowledge and awareness of the use of technology in population administration services, as well as network problems that often occur.